Dinamika Kelompok Dalam Pengelolaan Lembaga Filantropi: Studi Tentang Inovasi Dan Efektivitas Di Dompet Dhuafa - Azmi, Ulul; Suparto, Suparto (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Philanthropic institutions play a strategic role in supporting social development through community empowerment and the provision of social services. This study explores group dynamics in the management of Dompet Dhuafa, focusing on how group factors contribute to innovation and organizational management effectiveness. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and organizational document analysis. The research results show that effective communication, collaborative leadership, and adaptive conflict management are the main drivers of program innovation, such as the development of digital technology in fundraising. In addition, the effectiveness of the institution is influenced by accountability, transparency, and beneficiary satisfaction. This study provides practical recommendations to strengthen group dynamics in order to enhance innovation and sustainability in philanthropic institutions.